Robo-Advisory: An Investor’s Perception - Balwani, Nitin; Dash, Abhilas; Das, Aishwarya; Das, Lipsa; Misra, Siddharth; Ghose, Supriyo (International Journal of Psychosocial Rehabilitation, 2019)
Purpose: This research paper aims to examine the perception of individual investors towards the robo-advisory financial services and the performance of this innovative platform against human advisors.Design/ methodology/ approach: A survey method was employed and a response set from 167 investors were collected to probe into the perception of potential investors on the robo-advisory. The relationship between the perception and the robo-advisory was established using the regression analysis and the hypothesis was validated using ANOVA.Findings: The outcome of the study suggested that the investor’s prefer the robo-advisory financial services platform over human advisors as far as investment was concerned.Practical Implications: Clients and potential investors can avail an automated algorithm based investment platform. The robo-advisory platform can be enforced into the banking and insurance sectors for generating faster financial assistance and investment decision than a traditional human advisor.Originality/value: The novelty of this paper lies in the empirical evidence of the impact of potential investors on the robo-advisory. The successful implementation of the robo-advisory in Indian firms will help the common man to avail a low cost and high accuracy advisory facility.